0
$\begingroup$

In this post in the last method the factorials were factorized. But I don't quite understand how that works.

Lets say we have

$$ (-24)^{-1}+(6)^{-1} +(-2)^{-1}$$

modulo a prime $p$, for instance $7$. Then $(-24)^{-1} = 2$, $(6)^{-1} = 6$ and $(-2)^{-1} = 3$ (correct me if I'm wrong).
The sum is congruent to $11 \equiv 4$ modulo $7$ which is correct.

However, the factorized method multiplies $(-24)^{-1}$ by $8$ modulo $7$. That is $(-24)^{-1}$ (because $8 \equiv 1 \pmod 7$) which equals $2$.. that is wrong.

Am I doing something wrong here? Is $7$ an exception because $8$ is congruent to $1$?

$\endgroup$
1
$\begingroup$

I think the problem is a mistake that was pointed out in the comments. Note that

$$-24(-24)^{-1}\equiv1\pmod p$$ $$6[-4(-24)^{-1}]\equiv1\pmod p$$.

So we have $6^{-1}\equiv-4(-24)^{-1}$. Similarly, we have $(-2)^{-1}\equiv12(-24)^{-1}$. Therefore, we have

$$(-24)^{-1}+6^{-1}+(-2)^{-1}\equiv(-24)^{-1}(1-4+12)\equiv9(24)^{-1}$$

$\endgroup$
0
0
$\begingroup$

Not sure about the confusion

as $$-24\cdot2=-48\equiv1\pmod7\iff(24)^{-1}\equiv2$$

and as $8\equiv1\pmod7, $$$(-24)^{-1}\equiv(-24)^{-1}8\pmod7\equiv(-3)^{-1}\equiv2$$

as $-3\cdot2=-6\equiv1\pmod7$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.